Deep brain stimulation and stereotactic-assisted brain graft injection targeting fronto-striatal circuits for Huntington's disease: an update - Kinfe, Thomas Mehari; Del Vecchio, Alessandro; Nüssel, Martin; Zhao, Yining; Stadlbauer, Andreas; Buchfelder, Michael (Expert review of neurotherapeutics, 2022)
Introduction: Huntington's Disease as progressive neurological disorders associated with motor, behavioral, and cognitive impairment poses a therapeutic challenge in case of limited responsiveness to established therapeutics. Pallidal deep brain stimulation and neurorestorative strategies (brain grafts) scoping to modulate fronto-striatal circuits have gained increased recognition for the treatment of refractory Huntington's disease (HD).
CRIS-Team WoS Importer:2022-07-08
Keywords: Huntington´s disease; fronto-striatal circuits; chorea; parkinsonism; dystonia; globus pallidus externus/internus; deep-brain stimulation; striatum; brain grafts; unified Huntington´s disease rating scale (UHDRS); chorea; safety; efficacy; quality of life